2019
DOI: 10.1088/1741-2552/aaee9c
|View full text |Cite
|
Sign up to set email alerts
|

Coarse behavioral context decoding

Abstract: Objective. Current brain-computer interface (BCI) studies demonstrate the potential to decode neural signals obtained from structured and trial-based tasks to drive actuators with high performance within the context of these tasks. Ideally, to maximize utility, such systems will be applied to a wide range of behavioral settings or contexts. Thus, we explore the potential to augment such systems with the ability to decode abstract behavioral contextual states from neural activity. Approach. To demonstrate the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…Similar spectral power changes have also been observed in EEG and local field potential recordings across a wide variety of movement behaviors (Chung et al, 2018;Milekovic et al, 2015;Ofori et al, 2015;Tan et al, 2016). An important attribute of ECoG recordings is that the patients are being continuously monitored over long periods of time, often approximately a week, providing unique opportunities to collect long-term datasets during unconstrained, uninstructed movements (Alasfour et al, 2019;Chao et al, 2010;Gabriel et al, 2019;Vansteensel et al, 2013;Wang et al, 2018Wang et al, , 2016. However, the behavioral and neural variability of such spontaneous, naturalistic movements remains unexplored.…”
Section: Introductionmentioning
confidence: 53%
“…Similar spectral power changes have also been observed in EEG and local field potential recordings across a wide variety of movement behaviors (Chung et al, 2018;Milekovic et al, 2015;Ofori et al, 2015;Tan et al, 2016). An important attribute of ECoG recordings is that the patients are being continuously monitored over long periods of time, often approximately a week, providing unique opportunities to collect long-term datasets during unconstrained, uninstructed movements (Alasfour et al, 2019;Chao et al, 2010;Gabriel et al, 2019;Vansteensel et al, 2013;Wang et al, 2018Wang et al, , 2016. However, the behavioral and neural variability of such spontaneous, naturalistic movements remains unexplored.…”
Section: Introductionmentioning
confidence: 53%
“…Similar spectral power changes have also been observed in EEG and local field potential recordings across a wide variety of movement behaviors [59][60][61][62][63]. An important attribute of ECoG recordings is that the patients are being continuously monitored over long periods of time, often approximately a week, providing unique opportunities to collect long-term datasets during unconstrained, uninstructed movements [64][65][66][67][68][69]. However, the behavioral and neural variability of such spontaneous, naturalistic movements remains unexplored.…”
mentioning
confidence: 80%
“…As sEEG targets deeper brain structures including limbic regions such as the amygdala, it is well-suited to detect and decode brain activity associated with such user states. Alasfour et al (2019) demonstrated the classification of abstract naturalistic behavioral contexts from ECoG and sEEG recordings, which could be used to adapt interfaces to the coarse behavioral context of users in the future. Sani et al (2018) showed that mood variations during natural behavior can be decoded from intracranial recordings (including sEEG).…”
Section: Passive Bcimentioning
confidence: 99%